Total Antioxidant Activity, Total Phenolic and Flavonoid Contents of Eggplant (Solanum melongena L.), and Six of its Wild Relatives in the Philippines - Callano, Khris June L. (Silliman Journal, 2022)
In the Philippines, phytochemical study on eggplant and its wild relatives has not yet been explored. The total phenolic and flavonoid contents as well as the total antioxidant capacity of seven Solanum species in the Philippines were assessed through Folin-Ciocalteau assay, aluminum chloride colorimetic method and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, respectively. S. americanum and S. melongena were noted to produce the highest amount of phenols (96.43 and 74.38 mg GAE/g DW, respectively) and flavonoids (33.58 and 31.61 mg RUE/g DW, respectively) in their fruits. These two Solanum species also revealed the highest radical scavenging activity (8.61% and 6.85%, respectively). On the other hand, S. capsicoides was observed to produce low amount of phenols (54.31 mg GAE/g DW) and flavonoids (12.54 mg RUE/g DW), and eventually showed weak radical scavenging activity (3.76%). Correlation analysis suggested that the antioxidant capacity of the seven Solanum species was positively correlated to their total phenolic and flavonoid contents.